2014
DOI: 10.1002/cncr.28894
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in urologist visits among elderly men with prostate cancer: A cohort analysis of patient‐related and county of residence‐related factors

Abstract: BACKGROUND: Factors contributing to the lower likelihood of urologist follow-up among African American (AA) men diagnosed with prostate cancer may not be strictly related to patient factors. The authors investigated the relationship between crime, poverty, and poor housing, among others, and postdiagnosis urologist visits among AA and white men. METHODS: The authors used linked cancer registry and Medicare claims data from 1999 through 2007 for men diagnosed with American Joint Committee on Cancer stage I to I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…Consistent with this study, in a SEER-Medicare cohort, Onukwugha et al reported that Black men with prostate cancer were less likely to see a urologist while married men or those residing in an urban residence were more likely to see a urologist within 1 year of diagnosis ( Onukwugha et al., 2014 ). The results of this study build on Onukwugha et al by examining follow-up visits within 6 months and during the 2nd year in addition to 1st year.…”
Section: Recommendations and Limitationssupporting
confidence: 64%
See 2 more Smart Citations
“…Consistent with this study, in a SEER-Medicare cohort, Onukwugha et al reported that Black men with prostate cancer were less likely to see a urologist while married men or those residing in an urban residence were more likely to see a urologist within 1 year of diagnosis ( Onukwugha et al., 2014 ). The results of this study build on Onukwugha et al by examining follow-up visits within 6 months and during the 2nd year in addition to 1st year.…”
Section: Recommendations and Limitationssupporting
confidence: 64%
“…Few studies have examined receipt of follow-up care specifically among prostate cancer survivors. In a SEER-Medicare study, Onukwugha et al observed that 16% of men with stage I to stage III prostate cancer did not see a urologist within 1 year of diagnosis ( Onukwugha et al, 2014 ). This study builds on previous research by examining predictors of follow-up among prostate cancer patients, including men diagnosed before 65 years of age, in three specific periods including: within 6 months, in the 1st year, and in the 2nd year post surgery.…”
Section: Background and Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geographical and prostate cancer factors found in selected disparity studies have been summarized in the Table. [12][13][14][15][16][17][18][19][20][21][22][23][24][25]…”
Section: Resultsmentioning
confidence: 99%
“…52 In the field of prostate cancer, research using GIS approaches has been conducted to investigate diagnoses, management, and treatment outcomes across different geographical levels, such as counties, census division/tracts, cancer registry areas, and other aggregate geographical scales. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] Cockburn et al 53 used the GIS to geocode the historical residential addresses of individuals and measured the association between ambient exposure to pesticide and incidence rates of prostate cancer in California. They found a positive relationship between prostate cancer and ambient pesticide exposure in and around homes in intensely agricultural areas.…”
Section: Geographical Information System and Its Role In Disparity Rementioning
confidence: 99%